A team level participatory approach aimed at improving sustainable employability of long-term care workers: a study protocol of a randomised controlled trial - Ceciel H. Heijkants; Madelon L. M. van Hooff; Sabine A. E. Geurts; Cécile R. L. Boot (BMC, 2022)
Abstract Background Staff currently working in long-term care experience several difficulties. Shortage of staff and poor working conditions are amongst the most prominent, which pose a threat to staff's sustainable employability. To improve their sustainable employability it is important to create working conditions that fulfil workers' basic psychological need for autonomy, relatedness and competence in line with Self-Determination Theory. Since many long-term care organisations work with self-managing teams, challenges exist at team level. Therefore, there is a need to implement an intervention aimed at maintaining and improving the sustainable employability of staff on team level. Methods We developed a participatory workplace intervention, the Healthy Working Approach. In this intervention teams will uncover what problems they face related to autonomy, relatedness and competence in their team, come up with solutions for those problems and evaluate the effects of these solutions. We will evaluate this intervention by means of a two-arm randomized controlled trial with a follow-up of one year. One arm includes the intervention group and one includes the waitlist control group, each consisting of about 100 participants. The primary outcome is need for recovery as proxy for sustainable employability. Intervention effects will be analysed by linear mixed model analyses. A process evaluation with key figures will provide insight into barriers and facilitators of the intervention implementation. The Ethical Committee Social Sciences of the Radboud University approved the study. Discussion This study will provide insight in both the effectiveness, and the barriers/facilitators of the implementation process of the Healthy Working Approach. The approach is co-created with long-term care workers, focuses on team-specific challenges, and is rooted in the evidence-based participatory workplace approach and Self-Determination Theory. First results are expected in 2022. Trial registration Netherlands Trial Register, NL9627 . Registered 29 July 2021 - Retrospectively registered.